METHODOLOGY OF EDUCATION OF CHILDREN WITH HEARING DEFECTS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The branch of special pedagogy is deaf pedagogy (Lat. "surdus"- deafness), a science that studies the development of hearing-impaired children and adults, and the laws of their education (the branch of special pedagogy)